2018
DOI: 10.1007/s11356-018-2413-4
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides in indoor and outdoor residential dust: a pilot study in a rural county of Taiwan

Abstract: We conducted a pilot study to examine pesticides in dust of homes in a rural county of Taiwan. A total of 56 homes of pregnant women were included in the study. Indoor and outdoor dust was collected by a vacuum sampler and a dustpan/brush set, respectively. Nine pesticides were selected for analysis on gas chromatography-mass spectrometry with the detection limits being 0.088 ng/g or lower. The most detected pesticides were cypermethrin and chlorpyrifos, which appeared in 82.7 and 78.8% of indoor samples and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 38 publications
7
29
2
Order By: Relevance
“…This result of PYRs suggests that the subjects should have been exposed to insecticides environmentally more than via the dietary ingestion route because all but cypermethrin are used for environmental sanitation only. The finding of a high detection rate and high mean concentration of cypermethrin is consistent with our previous work indicating cypermethrin as the most frequently detected PYR in house dust [38]. Prallethrin is commonly known for the active ingredient of electric mosquito incense, which customers usually use overnight for mosquito prevention.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result of PYRs suggests that the subjects should have been exposed to insecticides environmentally more than via the dietary ingestion route because all but cypermethrin are used for environmental sanitation only. The finding of a high detection rate and high mean concentration of cypermethrin is consistent with our previous work indicating cypermethrin as the most frequently detected PYR in house dust [38]. Prallethrin is commonly known for the active ingredient of electric mosquito incense, which customers usually use overnight for mosquito prevention.…”
Section: Discussionsupporting
confidence: 91%
“…The lower detection rates shown in the U.S. studies are rational because the ban of chlorpyrifos in domestic use became effective in 2000. A similar comparison result was made in our previous work [38], demonstrating relatively low levels of chlorpyrifos in the dust of U.S. houses compared to our Taiwanese data. As chlorpyrifos and terbufos have been banned for domestic use respectively in the U.S. and in China and European Union [41], exposure to OPs should be of concern in Taiwan.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With such substantial consumption in quantity, residues of insecticides present in residential environments are nearly inevitable. A pilot study conducted in Taiwan has demonstrated high detection rates of chlorpyrifos and cypermethrin in house dust, reflecting frequent use of insecticides in the homes [2]. Residues of insecticides in the home environment serve as a potential health threat to young children, because their hand-to-mouth behaviors may enhance the non-dietary ingestion exposure to insecticides [3].…”
Section: Introductionmentioning
confidence: 99%